Iron deﬁciency and schooling attainment in Peru - Chong, Alberto; Cohen, Isabelle; Field, Erica; Nakasone, Eduardo; Torero, Máximo (International Association of Agricultural Economists, 2015)
A key question in development economics is whether nutritional deficiencies generate intergenerational poverty traps by reducing the earnings potential of children born into poverty. To assess the causal influence on human capital of one of the most widespread micronutrient deficiencies, supplemental iron pills were made available at a local health center in rural Peru and adolescents were encouraged to take them up via classroom media messages. Results from school administrative records provide novel evidence that reducing iron deficiency results almost immediately in a large and significant improvement in school performance. For anemic students, an average of 10 100mg iron pills over three months improves average test scores by 0.4 standard deviations and increases the likelihood of grade progression by 11%. Supplementation also raises anemic students’ aspirations for the future. Both results indicate that cognitive deficits from iron-deficiency anemia contribute to a nutrition-based poverty trap. Our findings also demonstrate that, with low-cost outreach efforts in schools, supplementation programs offered through a public clinic can be both affordable and effective in reducing rates of adolescent IDA. Chong, Alberto; Cohen, Isabelle; Field, Erica; Nakasone, Eduardo; Torero, Maximo